Activation of Astrocytes and Microglial Cells and CCL2/CCR2 Upregulation in the Dorsolateral and Ventrolateral Nuclei of Periaqueductal Gray and Rostral Ventromedial Medulla Following Different Types of Sciatic Nerve Injury - Dubový, Petr; Klusáková, Ilona; Hradilová-Svíženská, Ivana; Joukal, Marek; Boadas-Vaello, Pere (Frontiers in Cellular Neuroscience, 2018)
Peripheral nerve injuries may result in cellular and molecular changes in supraspinal structures possibly involved in neuropathic pain maintenance. Activated glial cells in specific supraspinal subregions may affect the facilitatory role of descending pathways. Sterile chronic compression injury (sCCI) and complete sciatic nerve transection (CSNT) in rats were used as neuropathic pain models to study the activation of glial cells in the subregions of periaqueductal gray (PAG) and rostral ventromedial medulla (RVM). Molecular markers for activated astrocytes (GFAP) and microglial cells (OX42) were assessed by quantitative immunohistochemistry and western blotting. The cellular distribution of CCL2/CCR2 was monitored using immunofluorescence. sCCI induced both mechanical and thermal hypersensitivity from day 1 up to 3 weeks post-injury. Unilateral sCCI or CSNT for 3 weeks induced significant activation of astrocytes bilaterally in both dorsolateral (dlPAG) and ventrolateral PAG (vlPAG) compared to naïve or sham-operated rats. More extensive astrocyte activation by CSNT compared to sCCI was induced bilaterally in dlPAG and ipsilaterally in vlPAG. Significantly more extensive activation of astrocytes was also found in RVM after CSNT than sCCI. The CD11b immunopositive region, indicating activated microglial cells, was remarkably larger in dlPAG and vlPAG of both sides from sCCI- and CSNT-operated rats compared to naïve or sham-operated controls. No significant differences in microglial activation were detected in dlPAG or vlPAG after CSNT compared to sCCI. Both nerve injury models induced no significant differences in microglial activation in the RVM. Neurons and activated GFAP+ astrocytes displayed CCL2-immunoreaction, while activated OX42+ microglial cells were CCR2-immunopositive in both PAG and RVM after sCCI and CSNT. Overall, while CSNT induced robust astrogliosis in both PAG and RVM, microglial cell activation was similar in the supraspinal structures in both injury nerve models. Activated astrocytes in PAG and RVM may sustain facilitation of the descending system maintaining neuropathic pain, while microglial activation may be associated with a reaction to long-lasting peripheral injury. Microglial activation via CCR2 may be due to neuronal and astrocytal release of CCL2 in PAG and RVM following injury.